Analisis Penurunan Daya Dukung Tiang Tunggal pada Tanah yang Berpotensi Mengalami Likuifaksi di Kota Denpasar, Bali - I Made Wahyu Pramana; I Wayan Arya; I Wayan Wiraga; IGAG Surya Negara Dwipa RS (Jurnal Talenta Sipil, 2023)
In Indonesia, earthquakes occur very frequently. As a result of the earthquake, the safety of building structures against earthquakes really needs to be taken into account in the analysis of calculating the factor of safety. Apart from the effect of the earthquake on the superstructure, the effect of the earthquake on the substructure must also be considered. One of the substructure failures that can occur in the substructure due to an earthquake is a soil liquefaction where the soil experiences a loss/decrease in the bearing capacity of the soil as a result of the earthquake. This study used a quantitative method by conducting soil investigations and taking soil samples from the field. The results of the soil investigation will be used in calculating the potential for liquefaction of the soil layers and the axial bearing capacity of single pile foundations before and during liquefaction. At the study site, the dominant soil is loose sand with a high ground water table. The soil has the potential to experience liquefaction from a depth of 1.5 m to 13 m. This study modeled 2 pile models where both of them experienced a decrease in the axial pile bearing capacity respectively: 93% and 79%.